Mitochondria-Targeting Immunogenic Cell Death Inducer Improves the Adoptive T-Cell Therapy Against Solid Tumor - Jiang, Qingzhi; Zhang, Chi; Wang, Huilan; Peng, Tao; Zhang, Li; Wang, Yang; Han, Weidong; Shi, Chunmeng (Frontiers in Oncology, 2019)
Cancer immunotherapy including adoptive T cell therapy (ACT) has been widely used in the clinic and is highly beneficial for patients with hematological malignancies; however, it remains a challenge to develop effective immunotherapy strategies for the treatment of solid cancers, due to the inefficiency of the immune response and the immunosuppressive tumor microenvironment (TME). Immunogenic cell death (ICD) converts dying cancer cells into a therapeutic vaccine and stimulate a systemic antigen-specific antitumor immune response, which can effectively subvert the immunosuppressive TME and enhance the efficiency of immune responses, relative to conventional immunotherapeutic regimens. However, the application of traditional inducers of ICD in anti-cancer immunotherapy has been limited because of low levels of ICD induction and lack of tumor-targeting accumulation. Mitochondria are important for tumor-targeting strategies and emerging as organelles with key roles in the immune system. We hypothesized that alteration of mitochondria in cancer cells could be an important target for the development of an efficient ICD inducer for use in cancer immunotherapy. Here, we report the evaluation of a mitochondria-targeted small molecule, IR-780, that acts as an ICD inducer and exhibits exceptional antineoplastic activity. IR-780 specifically accumulated in tumor cells to elicit ICD in vitro and in vivo, effectively suppressed tumor growth and lung metastasis, and enhanced adoptive T-cell therapy effects against solid tumors in mouse models. These anticancer effects were linked to dendritic cell maturation and synergistic effector T cell priming and infiltration into tumors. The underlying mechanism involves direct targeting of the mitochondria by IR-780, to destroy cancer cells, including drug-resistant cancer cells, leading to full exposure of TAAs, thereby enhancing antigen-specific antitumor immune responses. These features of IR-780 suggest that it has the advantages of leading to complete TAA exposure and stimulation of efficient antitumor immune responses in the TME. IR-780 has potential for use as a preparative ICD inducer, in combination with conventional immunostimulatory regimens for cancer immunotherapy, particularly in the context of solid tumor treatment.